TOXICITY OF DYES AND DYE INTERMEDIATES - Waheed, Shahina; Khan, Ghulam Rabbani (Biological Sciences - PJSIR, 2004)
Dyes and pigments are mostly colored substances used for coloration.The chemicals used for their synthesis are hazardous for human life. The metabolism occurs primarily in liver and the metabolites formed are transported in the blood where they can form protein adduct or undergo renal filtration in urinary bladder lumens where at acidic pH, they can react covalently with DNA and the carcinogen DNA adducts formed cause disorders in the whole metabolic reactions. Many carcinogenic/ mutagenic hazards, which occur in the body, have been summarized for public awareness.